Synthesis and Optical Properties of SrMgAl10O17:Mn4+ for Phosphor Conversion Solid State Lighting Devices - Kim Chi, Nguyen Thi; Hung, Nguyen Duy (VNU Journal of Science: Mathematics - Physics; Vol 35 No 4, 2019)
Recently, red-emitting Mn 4+ activated oxide phosphors have been a promising material to improve color rending and reduce price of warm white light emitting diodes (w-WLED). Thus, to find suitable red-emitting phosphors applied for w-WLEDs, SrMgAl 10 O 17 :Mn 4+ (SMA:Mn 4+ ) phosphors were synthesized by co-precipitation method. The effects of annealing temperature on these phosphors’ crystal structure, morphology and photoluminescence properties were investigated. The phosphors were broad excitation bands in the 250-600 nm wavelength range with peaks at 320, 400, and 470 nm. Under excitation of 320 nm wavelength, the phosphors emitted efficient red light around 658 nm. The luminescence mechanism was studied in detail. The optimal doping concentration of Mn 4+ ions was about 1.2 mol.%. Thus, the SMA:Mn 4+ phosphors would have great potential for applying in near-UV (320, 400 nm) and blue (470 nm) phosphor conversion LED.